Pola Komunikasi Keluarga dalam Menghadapi Anak Kecanduan Game Mobile Legends di Kelurahan Kebagusan - Muhammad Dhika Fachrezi; Bonardo Marulitua Aritonang; Muhammad Ismail Alif (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The phenomenon of Mobile Legends addiction among children in Kebagusan has generated significant social and academic consequences, highlighting the crucial role of family communication patterns in addressing this issue. This study aims to analyze parental communication strategies in dealing with children addicted to Mobile Legends. Employing a descriptive qualitative method, data were collected through in-depth interviews, observation, and documentation with four housewives as key informants. The findings reveal that the dominant communication pattern is democratic, characterized by openness, empathy, emotional support, and positive attitudes that foster dialogue within the family. This approach proved effective in reducing tensions, strengthening emotional bonds, and encouraging children to be more receptive to parental guidance. The study suggests that the democratic communication approach significantly mitigates the negative effects of digital addiction. Additionally, it emphasizes the importance of creating an open, supportive, and understanding environment at home, where children feel comfortable discussing their digital habits. In conclusion, democratic communication plays a vital role in overcoming digital addiction among children and offers practical implications for families to cultivate healthy interactions in the digital era.